Laboratory studies of the life cycle and behaviour of Amblyomma Variegatum (Fabricus,1794) (Acarina:ixodidae) (1990)
Amblyomma variegatum is a 3-host tick parasitising livestock in Nigeria. It is of great economic importance because it is a known vector of disease-causing microorganisms, such as Dermatophilus congolensis, Theileria mutans and cowdria ruminatium. It has a long life cycle which in the laboratory at 25 °C and the relative humidity of 85% lasts 160-200 days. It was observed that the longest developmental period occurred at the egg stage(eggs are laid on the ground). This makes this stage the most vulnerable, considering that they are the ones more exposed to climatic and enviromental hazards.